The Growth of MSE: The Effect of Financial Literacy and Access to Finance with Digital Finance and Usage of Digital Technology as Mediators - Zaragoza, Merlin Grace Panggabean; Pramesti, Muthia (Jurnal Manajemen Teknologi, 2025)
Abstract. This research was conducted to examine the effect of financial literacy and access to finance on the growth of micro-enterprises in Indonesia, with digital finance and the use of digital technology as mediation. This study uses a quantitative method with Indonesian micro-enterprises as respondents. Sampling obtained a total of 178 respondents, which was carried out by distributing questionnaires to the large community of MSEs: Jakpreneur and BRI Growprenuer. All data that has been collected is processed using the PLS-SEM method. The study results show that financial literacy and access to finance significantly influence the growth of micro-enterprises in Indonesia. The mediating role of digital finance and the usage of digital technology also significantly mediate the relationship between access to finance and micro-enterprise growth. Keywords: Financial literacy, access to finance, business growth, digital financial services, use of digital technology